Platelet Aggregation and Mental Stress Induced Myocardial Ischemia: Results from the REMIT Study - Jiang, Wei (Am Heart J, 2014)
BACKGROUND: Mental stress-induced myocardial ischemia (MSIMI) is common in patients with ischemic heart disease (IHD) and associated with a poorer cardiovascular prognosis. Platelet hyperactivity is an important factor in acute coronary syndrome. This study examined associations between MSIMI and resting and mental stress-induced platelet activity. METHODS: Eligible patients with clinically stable IHD underwent a battery of 3 mental stress tests during the recruitment phase of REMIT (Responses of Myocardial Ischemia to Escitalopram Treatment) study. MSIMI was assessed by echocardiography and electrocardiography. Ex vivo platelet aggregation in response to ADP, epinephrine, collagen, serotonin, and combinations of serotonin plus ADP, epinephrine, and collagen were evaluated as was platelet serotonin transporter expression. RESULTS: Of the 270 participants who completed mental stress testing, and had both resting and post-stress platelet aggregation evaluation, 43.33% (N=117) met criteria for MSIMI and 18.15% (N=49) had normal left ventricular response to stress (NLVR). The MSIMI group, relative to the NLVR groups, demonstrated heightened mental stress-induced aggregation responses, as measured by area under the curve, to collagen 10 μM (6.95[5.54] vs. −14.23[8.75].; p=0.045), epinephrine 10 μM (12.84[4.84] vs. −6.40[7.61].; p=0.037) and to serotonin 10 μM plus ADP 1 μM (6.64[5.29] vs. −27.34[8.34]; p < .001). The resting platelet aggregation and serotonin transporter expression, however, were not different between the two groups. CONCLUSIONS: These findings suggest that the dynamic change of platelet aggregation caused by mental stress may underlie MSIMI. While the importance of these findings requires additional investigation, they raise concern given the recognized relationship between mental stress-induced platelet hyperactivity and cardiovascular events in patients with IHD.